Complete PET: Workbook with answers - May P. Peter (Cambridge, Cambridge University Press, 2010)
Complete PET\s a brand new course for the PET exam. It combines the very best in contemporary classroom practice with stimulating topics aimed at teenagers and young adults. The course covers every part of the PET exam in detail providing preparation, practice, information and advice to ensure that students are fully prepared for every part of the exam. Informed by Cambridge's unique searchable database of real exam scripts, the Cambridge Learner Corpus*, and providing an official PET past exam paper from Cambridge ESOL, Complete PET\s the most authentic PET exam preparation course available. Complete PET Workbook with answers with Audio CD: contains 12 topic-based units for homework and self-study, providing additional exam style practice and further practice of the grammar and vocabulary taught in the Student's Book includes 12 'Vocabulary Extra' pages, to provide revision and further practice of the vocabulary contained in the Student's Book. includes exercises targeting common PET candidate problem areas, using data from the Cambridge Learner Corpus. provides extra listening practice to develop confidence in tackling the PET Listening Paper includes an audio CD containing all the listening material for the Workbook contains an answer key and recording scripts.